2016
DOI: 10.1016/j.mayocp.2015.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Centromedian-Parafascicular Complex Deep Brain Stimulation for Tourette Syndrome

Abstract: Deep brain stimulation (DBS) of the thalamic centromedian/parafascicular (CM-Pf) complex has been reported as a promising treatment for patients with severe, treatment resistant Tourette syndrome (TS). In this study, safety and clinical outcomes of bilateral thalamic CM-Pf DBS were reviewed in a series of twelve consecutive patients with medically refractory TS, eleven of whom met the criteria of post-surgical follow-up at our institution for at least two months. Five subjects were followed for a year or longe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Nonetheless, adolescence is a crucial period for social, emotional and educational development and preventing younger patients with severe debilitating TS receiving treatment could impact negatively on independence and wellbeing into adult life. This is supported by beneficial reports in younger patients including a 17 year old with SIBs that prevented full time school attendance who showed markedly improved social integration post DBS [ 37 ]. Consequently, recent recommendations argue against strict age criteria and suggest that younger patients should be reviewed on a case by case basis, involving a local ethics committee.…”
Section: Literature Reviewsupporting
confidence: 62%
See 1 more Smart Citation
“…Nonetheless, adolescence is a crucial period for social, emotional and educational development and preventing younger patients with severe debilitating TS receiving treatment could impact negatively on independence and wellbeing into adult life. This is supported by beneficial reports in younger patients including a 17 year old with SIBs that prevented full time school attendance who showed markedly improved social integration post DBS [ 37 ]. Consequently, recent recommendations argue against strict age criteria and suggest that younger patients should be reviewed on a case by case basis, involving a local ethics committee.…”
Section: Literature Reviewsupporting
confidence: 62%
“…Adverse effects included a scalp erosion due to compulsive picking, and an abdominal haematoma. These and other open label studies [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] are outlined in Table 1 and strongly indicated that thalamic stimulation may have a beneficial therapeutic role in TS for both tic severity as well as comorbid symptoms.…”
Section: Literature Reviewmentioning
confidence: 85%
“…An expansion of this series was recently published, including additional targets (85). As Table 1 shows, results from double-blinded randomized controlled trials and single-case studies or small surgical series tend to support the effectiveness of intralaminar thalamus DBS for TS (70–72, 75, 7779, 8183, 86). …”
Section: Clinical Outcomes Of Cm-pf Dbs For Tsmentioning
confidence: 85%
“…To date, the majority of TS DBS treatment studies has focused on the thalamus due to its strategic location between motor areas of the cerebral cortex and motorrelated subcortical structures, particularly the basal ganglia and cerebellum [33,34]. A retrospective study of several patients with refractory TS and psychiatric comorbidities reported that DBS of the thalamic centromedian-parafascicular (CM-Pf) complex was associated with a 46% improvement in motor tics and 52% improvement in phonic tics, as measured by the Yale Global Tic Severity Scale (YGTSS) at follow-up (mean duration: 26 months) [34]. Moreover, DBS of this thalamic region markedly improved the patients' social, occupational, and educational functioning.…”
Section: Single Target Thalamusmentioning
confidence: 99%
“…In general, DBS of the thalamus has been well tolerated, but patient risk and adverse side effects remain an issue of concern. Reported side effects include the transient blurring of vision, dysarthria, recurrent tension headache, and a single seizure-like episode (after DBS of the CM-Pf [34,36]). Disturbances of eye motility have also been documented, as well as impaired fine motor skills, particularly following DBS of the ventral anterior and ventrolateral motor thalamic regions [38].…”
Section: Single Target Thalamusmentioning
confidence: 99%